MYSM1 attenuates osteoarthritis by recruiting PP2A to deubiquitinate and dephosphorylate RIPK2 - Kang Wei; Chuankun Zhou; Zixing Shu; Xingru Shang; Yi Zou; Wei Zhou; Huanhuan Xu; Yulin Liang; Tian Ma; Xuying Sun; Jun Xiao (Bone Research)
Abstract Osteoarthritis (OA), the most prevalent degenerative joint disease, is marked by cartilage degradation and pathological alterations in surrounding tissues. Currently, no effective disease-modifying treatments exist. This study aimed to elucidate the critical roles of Myb-like, SWIRM, and MPN domains 1 (MYSM1) and its downstream effector, Receptor-interacting protein kinase 2 (RIPK2), in OA pathogenesis and the underlying mechanisms. Our findings revealed reduced MYSM1 levels in the cartilage of OA patients and mouse models. Genetic or adenovirus-induced MYSM1 knockout exacerbated OA progression in mice, whereas MYSM1 overexpression mitigated it. Mechanistically, MYSM1 inhibited the NF-κB and MAPK signaling pathways. Conversely, downstream RIPK2 significantly increased OA-like phenotypes and activated the NF-κB and MAPK pathways. The Ripk2 S176D mutation accelerated OA pathogenesis, while Ripk2 silencing or Ripk2 S176A mutation deactivated NF-κB and MAPK pathways, counteracting the role of MYSM1. MYSM1 deubiquitinates and dephosphorylates RIPK2S176 by recruiting protein phosphatase 2 A (PP2A). These results suggest that targeting MYSM1 or downstream RIPK2 offers promising therapeutic potential for OA.